Effect of Field of View and Resolution in Detection of Horizontal Root Fractures in CBCT images: An In Vitro Study - Sharifi Shoshtari, Sanaz; Shams, Nasim; Dabbaghi, Arash; Rohani, Ali; Dadollahi, Makan; Khosravi, Negin (Iranian Endodontic Journal, 2018)
Introduction: New cone-beam computed tomography (CBCT) devices are capable of imaging with different resolutions and field of views (FOVs), in which higher resolutions and FOVs impose a higher dose to the patient. This study was an attempt to investigate the detection accuracy from different FOVs and resolutions in detection of horizontal root fractures. Methods and Materials: Through this experimental study, in five different field of views (FOV) and resolutions (voxel size) of New Tom VGi CBCT (Italy) system was used to scan fifty teeth with horizontal root fractures in half of them. The images were evaluated by four observers (two maxillofacial radiologists and two general dentists) who recorded the presence or absence of horizontal root fractures. The data were analyzed by SPSS 22 software and MacNemar and kappa test were used to compare results with reality. Results: The highest sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy (AZ) were attributed to 8×8 FOV and high resolutions (0.125 mm voxel size) but the difference between sensitivity, specificity, PPV and NPV was not significant. Kappa values for inter-observer agreement between radiologists and general dentists and also intra-observer agreement were in excellent ranges. The highest Kappa in both cases was attributed to 8×8 FOV and high resolutions. Conclusion: There was no significant difference to diagnose of horizontal root fracture between two observer groups and for all of the FOVs and voxel sizes. Keywords: Cone-Beam Computed Tomography; Field of View; Horizontal Root Fracture